Limb-Girdle Muscular Dystrophy Type 2H Associated with Mutation in TRIM32, a Putative E3-Ubiquitin–Ligase Gene - Frosk, Patrick (The American Society of Human Genetics, 2002)
Limb-girdle muscular dystrophy type 2H (LGMD2H) is a mild autosomal recessive myopathy that was first described in the Manitoba Hutterite population. Previous studies in our laboratory mapped the causative gene for this disease to a 6.5-Mb region in chromosomal region 9q31-33, flanked by D9S302 and D9S1850. We have now used additional families and a panel of 26 microsatellite markers to construct haplotypes. Twelve recombination events that reduced the size of the candidate region to 560 kb were identified or inferred. This region is flanked by D9S1126 and D9S737 and contains at least four genes. Exons of these genes were sequenced in one affected individual, and four sequence variations were identified. The families included in our study and 100 control individuals were tested for these variations. On the basis of our results, the mutation in the tripartite-motif–containing gene (TRIM32) that replaces aspartate with asparagine at position 487 appears to be the causative mutation of LGMD2H. All affected individuals were found to be homozygous for D487N, and this mutation was not found in any of the controls. This mutation occurs in an NHL (named after the proteins NCL1, HT2A, and LIN-41) domain at a position that is highly conserved. NHL domains are known to be involved in protein-protein interactions. Although the function of TRIM32 is unknown, current knowledge of the domain structure of this protein suggests that it may be an E3-ubiquitin ligase. If proven, this represents a new pathogenic mechanism leading to muscular dystrophy.